Brownfield Transformation in Fragile Territories An Interreg-Based Action Research - Modica, Marcello; Solero, Elena (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents and critically evaluates the results of a European territorial cooperation project addressing the planning challenge of brownfield transformation in fragile territories. Set against the backdrop of the current scenario of deindustrialisation in the European Alps, the book describes how to read and interpret the spatial condition of industrial brownfields in peripheral mountain areas as complex transformation sites. Through key theoretical references, well-documented experiences and field activities, the book explores and advances an innovative methodology of design-based participatory planning conceived specifically for fragile socioeconomic and environmental contexts. The empirical basis for such a methodological exploration is provided by four pilot sites distributed between Austria, Italy, France and Slovenia, identified in the cooperation project as highly representative and recurring situations. The book includes a comparative review of the work carried out for the pilot sites, as well as the planning outcomes generated, providing a clear and operative reference for scholars, professionals and public officers called to face similar experiences.
Keywords: Human geography; Sustainability; Urban economics; Sociology, Urban; Human Geography; Sustainability; Urban Economics; Urban Sociology